MAKNA SIMBOLIK TARI REYOG GEMBLUK TULUNGAGUNG - Nur Rokhim (Gelar : Jurnal Seni Budaya, 2013)
Reyog Gembluk Dance was a tradiotional performing art that raised and developed and belongsto Tulungagung society. The dance was performed by six dancers carrying Gembluk as the portraitwarriorss sent by of the king of Bugis’s to propose Kediri Proncess, Dewi Kilisuci. Reyog GemblukDance moves was full of symbols in interpreting the moves of Bugis warriors carrying task fromtheir king. The instruments of Reyog Gembluk Dance were the symbols of Bebana from the kingof Bugis for Dewi Kilisuci. The symbols in Reyog Gembluk Dance were society convention as theaesthetic expressions tool to strengthen interaction weaves among them. Symbolic expressionsin arts were the communication medium to ourselves, society, and environment. The meaning ofReyog Gembluk Dance was based on an event or story that happened in society as the symbolismtradition in arts and culture. In arts, historical facts was not meant to be proven. The most importantwas there were space for symbolized message deliverance. Moral messages that being expressedin a fine and beautiful way through arts were more acceptable as a way of life. Reyog GemblukDance was full of symbols with moral messages, motivation, and spirit in dealing with life problems.